Systematic Literature Review: Impact of Post-Traumatic Stress Disorder on Entrepreneurial Intentions - Mahmood, Rana Shahid; Sabir, Raja Irfan; Masud, Shahjahan (Journal of Applied Research and Multidisciplinary Studies, 2025)
This systematic literature review aimed to explore the consequences of post- traumatic stress disorder (PTSD) due to traumatic childbirth in relation to emotional intelligence (EI) and social influence. Women make an extraordinary contribution to regional and national production. Furthermore, the United Nations (UN) Sustainable Development Goals (SDGs) highly emphasize the mental and physical health of women. Compulsive buying is a significant issue that causes emotional, financial, and social distress to individuals and their families. Entrepreneurial intentions play a crucial role since they serve as a precursor to entrepreneurial activities influencing both individual and economic outcomes. The review period encompassed researches published from January 2014 to December 2023. Through a comprehensive examination of the literature, this review identified key dimensions and variables used to investigate the association between post- traumatic stress and entrepreneurial intentions. Several dimensions were considered in the reviewed literature including psychological factors, individual characteristics, and environmental influences. Psychological factors encompassed variables, such as resilience, coping mechanisms, and cognitive appraisal of trauma. Individual characteristics included personality traits, past traumatic experiences, and levels of self-efficacy and motivation. Environmental influences encompassed socio-economic factors, social support networks, and cultural contexts. The variables utilized in the reviewed studies involved measures of post-traumatic stress symptoms, such as intrusive thoughts, avoidance behaviors, and hyperarousal. Entrepreneurial intentions were assessed through measures of entrepreneurial self-efficacy, desire for autonomy, risk-taking propensity, and intention to start or pursue entrepreneurial endeavors. The current study contributed to the understanding of how post-traumatic stress influences entrepreneurial intentions. Furthermore, it also highlighted the importance of considering psychological, individual, and environmental factors in research and interventions aimed at supporting individuals with post- traumatic stress who aspire to entrepreneurship.